2010
DOI: 10.1021/jp109600c
|View full text |Cite
|
Sign up to set email alerts
|

A High-Pressure Infrared Spectroscopic Study on the Interaction of Ionic Liquids with PEO-PPO-PEO Block Copolymers and 1,4-Dioxane

Abstract: We have investigated the effect of pressure on imidazolium C-H---O interactions in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide (EMI(+)TFSA(-))/L64 and EMI(+)TFSA(-)/1,4-dioxane mixtures. The addition of Pluronic L64 to EMI(+)TFSA(-) leads to appreciable changes in band frequencies and shapes of the imidazolium C-H stretching bands. A possible explanation is the formation of C-H---O interactions between imidazolium C-H groups and oxygen atoms of polyethylene oxides (PEOs). In other words, L64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…S1) as a probe for the intermolecular interactions in BmimPF 6 –γ‐BL mixture involving the ring sites of the cation though this is still not so well explored by Raman spectroscopy . Some IR studies suggest as well that the alkyl C―H stretching region 2800–3050 cm −1 could also be sensitive to the modulation of the interionic interactions induced by the dilution with molecular solvent despite it often remains intact under such perturbation . However, due to the severe overlap with the broad and complex profile of the C―H stretching vibrations of γ‐BL (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1) as a probe for the intermolecular interactions in BmimPF 6 –γ‐BL mixture involving the ring sites of the cation though this is still not so well explored by Raman spectroscopy . Some IR studies suggest as well that the alkyl C―H stretching region 2800–3050 cm −1 could also be sensitive to the modulation of the interionic interactions induced by the dilution with molecular solvent despite it often remains intact under such perturbation . However, due to the severe overlap with the broad and complex profile of the C―H stretching vibrations of γ‐BL (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Before going to a detailed analysis we should note that three possible scenarios of the behavior of the imidazolium ring C―H stretching wavenumbers have been observed in mixtures of imidazolium ILs with molecular solvents. Upon dilution of the neat IL with molecular solvent these scenarios include ( i ) a redshift in such systems as BmimBF 4 ‐MeOH, BmimBF 4 ‐DMSO, EmimTFSI‐PEO, BmimPF 6 /BF 4 ‐PEO, ( ii ) a blueshift in systems like EmimLac‐MeOH, EmimEtSO 4 ‐Acetone, BmimCl/MeSO 4 ‐EG, BmimTFA‐H 2 O/MeOH, or ( iii ) no apparent shift at all like in EmimTFSI‐MeOH, RmimBF 4 ‐EG, EmimTFSI‐DiOx, BmimBF 4 /PF 6 ‐AN systems. This can be systematized as that the redshift of the ring C―H vibrations is induced by the addition of donating solvents to weakly associated ILs where the solvent molecules can effectively compete with the anions for the ring C―H sites in order to establish stronger H‐bonds.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the C–H group is ubiquitous in organic and biological molecules, and water is the most important solution. The accumulated evidence has shown that C–H···O interaction acts as an important factor in crystal packing, structure–activity relationship, and conformation stabilization of molecules and molecular assemblies in both chemistry and biochemistry. , For example, the C–H···O hydrogen bond contributing an additional stability to self-assembled β-sheet formation in 1-acetamido-3-(2-primidinnyl) imidazolium has been reported . Recently, the strong C–H···O bifurcated interactions between the most acidic hydrogen atom of the cation imidazole ring and the oxygen atom of the anion were predicted in the room-temperature ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate using quantum chemical calculation .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been used as catalyst in chemical reaction [2], reaction media [3] and absorbent for metal extraction [4]. Despite exploring the new application of ionic liquids, researches on the interaction between ionic liquids and other organic substance such as water [5], acetonitrile [6], methanol [7] and polymer [8] are seen. In the point of view of interaction between ionic liquids and water, importance issue is included, because the presence of water in ionic liquids system strongly influences their physical and chemical properties, for instance, in viscosity, electrical conductivity, and reactivity [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%